PENDAMPINGAN PENULISAN ARTIKEL ILMIAH DALAM MEMBENTUK PROFESIONALISME GURU SMA DI KABUPATEN ACEH TAMIANG - Muhammad Yacob; Ratih Permana Sari; Dona Mustika (Global Science Society, 2020)
The purpose of this Community Service activity is to provide training to high school / vocational / MA physics and chemistry teachers on research management, including the preparation of proposals, conducting research, preparing scientific articles and how to publish articles in seminars and or journals. This training needs to be done because there is a gap between the assignment of teachers to write scientific papers with inadequate writing abilities and motivation so as to improve teacher professionalism and pedagogical competence. The teacher has the obligation to research and write scientific papers, but there are still limitations in implementing them. Training and practice in research management and preparation of scientific articles for teachers are still very much needed.Higher Education as a teacher-producing institution, as well as an institution that organizes research activities, has a moral obligation to conduct coaching. For this reason, community service programs to provide research management training and the preparation of scientific articles are the means adopted to overcome these problems.From the series of scientific article technical assistance activities it can be concluded as follows in general the development of professionalism of the teachers of SMA Negeri 2 Kejuruan Muda before conducting this activity still encountered some difficulties in writing scientific articles. During and after the mentoring activity, the teacher was very enthusiastic by opening the unsam e-journal website as examples of articles that had been published and following all the directions from the dedication team in conducting online journal submission techniques. Five scientific articles were produced that were suitable for publication in unsam e-journals and this was one of the final achievements of this dedication activity